Analysis of the Financial Performance Model of SMEs in Sei Semayang Village, Deli Serdang Regency - Novian Paisal Sitompul; Khaira Amalia Fachrudin; Nisrul Irawati (Universitas 17 Agustus 1945 Semarang, 2023)
This research aims to empirically prove the influence of financial literacy and financial technology on financial inclusion, the influence of financial literacy and financial technology on financial performance, the influence of financial inclusion on financial performance, and the influence of financial literacy and financial technology on financial performance through financial inclusion of SMEs in Sei Semayang Village, Deli Serdang Regency. The sample for this research was UKM Sei Semayang Village, Deli Serdang Regency which was selected using the purposive sampling method. Data analysis uses Structural Equation Modeling-Partial Least Square. The research results show that financial literacy and financial technology have a positive and significant effect on financial inclusion, financial literacy, and financial technology have a positive and significant effect on financial performance, financial inclusion has a positive and significant effect on financial performance, and financial inclusion mediates the effect of financial literacy and financial technology on financial performance.